Exploring the demographic, social, and neighbourhood predictors of loneliness among New Zealand’s older adults : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatu, New Zealand - Cannon, Tracy (Massey University, 2023)
Increased life expectancy has resulted in a larger proportion of older adults in the population. Through multiple changes, older adults’ social networks are shrinking. Consequently, these losses in social connections have resulted in loneliness. Loneliness is a complex and multi-faceted concept, consisting of emotional and social factors. Whilst loneliness has been linked to socio-demographics (age, gender, marital status, and health), few studies have explored the relationship between loneliness and social or neighbourhood influences. The study had three main objectives; to determine how lonely New Zealand’s older adult population is and the extent of emotional loneliness and social loneliness; to assess the socio-demographic predictors of loneliness among New Zealand’s older adult population; and to investigate whether objective measures of social and neighbourhood variables were related to loneliness. The sample was comprised of 4351 New Zealand adults aged 55–92 years old. Data was analysed using both bivariate correlations and logistic regression. The study found loneliness was most strongly related to gender, physical health, mental health, quality of life, housing and neighbourhood satisfaction, and volunteering. The study was limited to subjective evaluations and the impact of Covid-19 on loneliness in older adults has not been addressed. Some of the known predictors of loneliness were supported. The study also identified important social and neighbourhood determinants that have previously been overlooked, opening up avenues for future research into age-friendly environments.
Keywords: loneliness; emotional loneliness; social loneliness; older adults; social participation; neighbourhood; 520106 Psychology of ageing